Analisis Penyusunan Rencana Kerja di Satuan Kerja Perangkat Daerah (SKPD) Bagian BKAD Kota Medan - Adawiyah, Rabiatun; Dewi, Cindy Kumala; Helmi, Halimah; Nasution, Annio Indah Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The work plan is referred to as a process that has the potential to achieve the targets to be achieved for the next year while taking into account the potential, opportunities and obstacles that may arise, the work plan includes the vision and mission, as well as the goals and targets of an organization, and also regarding the main tasks and organizational functions, as well as programs and activities that include work planning to be carried out within one year. The preparation of work planning is the implementation of planning concepts that play a role in organizational managerial processes as a determining factor in the success of achieving goals and targets and achieving the vision and mission of an organization. Preparation of work plans in the Medan City Regional Finance and Asset Agency, compiled in sync using State Ministerial Regulation number 86 of 2017 concerning norms for planning, controlling and evaluating regional development, assessing norms on work plans including vision, mission, objectives, policies, events and activities will be implemented within one year. appropriate use identification and urgent disputes and use refers to income, ability to achieve performance, strategic planning, and synergy using national policies, against the aims and objectives of the acquisition sponsor at the Finance Agency and regional assets of the Medan City Levy Unit; Regional Work Units (SKPD) must produce capacity targets from the proposed activities in their budgets. Delegation of powers is not only the right to use the law, but also has consequences for that role. Regarding the use of financial data, SKPD must always know how much the APBN has entered. Keywords: BKAD, Work Plans, Regional Financial Control and Evaluation, Implementation of Regional Opinions.